Análise ergonômica de clínica-escola odontológica - uma proposta para profilaxia das LER/DORT - Duarte, Alexandre Castellar (2009)
The present study has as objective diagnoses the presence of conditions to come to develop LER/DORT in students of courses of Dentistry, that already carry out activities theoretical-practices in the respective clinic-school. In addition, was accomplished through solemnity-applicable questionnaire to verify characteristic symptomatologies. The sampling of the research involved 160 students of courses of Dentistry of public and private Universities. Given the importance of ergonomic studies for better performance and comfort throughout the workday, this study proposes, after analyzing the data collected, a number of considerations to be implemented for better productivity, performance conditions and adequate health comfort dental professional, using ergonomics. The results of the ergonomic analysis are presented in the form of preventive exercises for this profession